Społeczno-kulturowa wartość wykorzystania gier i zabaw w edukacji, integracji międzypokoleniowej i międzykulturowej według koncepcji Edmunda Bojanowskiego - Opiela, Maria (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The aim of the article is to show the socio-cultural value of applications of games and plays for the benefit of innovation in education, intergenerational and intercultural integration. The use of E. Bojanowski’s concept based on a critical edition of his notes in relation to the interdisciplinary achievements of social sciences and humanities serves to develop the theoretical basis for methodical solutions. On this basis, games and plays are presented as an element of both old and modern culture. The article also highlights their importance for the integral development and education of a person and the socio-cultural value of their application in intergenerational and intercultural integration. The socio-cultural value, need, principles and ways of using the heritage of the past and its applications in contemporary educational and cultural practice are shown and justified.